Students’ Perception of Learning Media Poster Material Structure and Function of Plants for Class VIII SMP - Yanita Nur Anggraheni; Much. Fuad Saifuddin (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2021)
Abstract The structure and function of plants need to be visualized in an exciting way, including through posters. Thepurpose of this study was to determine students' perceptions of the use of poster media in learning the structureand function of class VIII plants. The population includes students of class VIII SMPN 15 Yogyakarta with oneclass as a sample. The sample was taken using a purposive sampling technique. The research method used isdescriptive qualitative, with data collection techniques using a questionnaire. The questionnaire is on a Likertscale with four answer options: strongly agree, agree, disagree, and strongly disagree. The research results thathave been done show that the student's perception of the poster media is good. Students consider that the use ofposter media makes learning fun and efficient, following students' needs, triggers the spirit of learning, andincreases understanding and attractive presentation. Keywords: Biology learning, Internship student, Students’ perception, Poster media